Crazy little thing called love : a destination wedding novel - Vogt, Beth K. (Vogt, Beth K. Destination wedding novel., 2015)
"Vanessa runs into her ex-husband from her what-was-she-thinking teenage elopement while planning her destination wedding in Destin, Florida. Unexpected feelings arise and force her to reconsider what she thought was her biggest mistake and the possibility that God has other plans for her"--